Pengaruh Pelatihan Kerja dan Pengembangan Karir terhadap Kepuasan Kerja Aparatur Sipil Negara Puskesmas Pangaribuan pada Kecamatan Pangaribuan - Pakpahan, Sanjaya; Prayudi, Ahmad (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study was to determine the job training and career development on the job satisfaction of State Civil Apparatus at the Pangaribuan Community Health Center in Pangaribuan District. The population in this study was the state civil apparatus of the Pangaribuan Community Health Center, totaling 49 people. Sampling in this study was a saturated sample technique, because the population was below 100. So the sample in this study was 49 respondents. For the independent variables in this study were job training (X1) career development (X2). The dependent variable in this study was the job satisfaction of the State Civil Apparatus (Y). The research method used was a quantitative method and the data analysis used in this study was multiple linear regression analysis. Data processing was carried out with IBM SPSS Statistics 22. The results of the study showed that job training had an influence on the job satisfaction of the State Civil Apparatus with a t value of 2.711 and a significance value of 0.004 below 0.05, so the hypothesis in this study was accepted. Career development has an effect on the job satisfaction of State Civil Apparatus with a t value of 3.308 and the resulting significance value of 0.002 is below 0.05, so the hypothesis in this study is accepted.